Fetal Outcome among Hypertensive Disorders in Pregnant Women with Hyperuricemia - Munazza Mumtaz, Aneela Habib, Gulfishan Tariq, Maliha Fatima, Poonam Goswami, Aruna Kumari Hira (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: to determine the frequency of unfavorable fetal outcomes in pregnant women who had hypertensive disorders of pregnancy (HDP) and hyperuricemia. Patients and Methods: A total of 200 pregnant patients of age 18-40 years, attending OPD, ward, labor and emergency having hypertensive disorders having gestational age 24 to 40 weeks were included. Study was conducted from March 20,2020 to December 20, 2020. Patients having serum uric acid > 6.0 mg/dl were considered hyper-uricemic. All patients were followed to till delivery of baby to determine fetal outcomes with included; pre-term birth, still birth, low birth weight and early neonatal death. Results: The mean age was 28.16±5.01years, with gestational age of 35.45±3.21 weeks. Chronic hypertension was observed in 12 (6%), gestational hypertension 44 (22%), mild pre-eclampsia 31 (15.5%), moderate preeclampsia 52 (26%), superimposed pre-eclampsia in 14 (7%) and eclampsia was observed in 47 (23.5%) patients. Preterm was the commonest outcome that was observed in 96 (48%) patients, low birth weight in 70 (35%) patients, still birth in 33 (16.5%) patients and early neonatal death 25 (12.5%) patients. Conclusion: There is a high rate of adverse fetal outcomes in women presenting with HDP having hyperuricemia. So, measurement of serum uric acid concentration seems to be a useful test to predict fetal outcome in this high-risk population.